A new difference scheme for fractional cable equation and stability analysis - Karatay, Ibrahim; Kale, Nurdane (International Journal of Applied Mathematical Research, 2015)
We consider the fractional cable equation. For solution of fractional Cable equation involving Caputo fractional derivative, a new difference scheme is constructed based on Crank Nicholson difference scheme. We prove that the proposed method is unconditionally stable by using spectral stability technique.
Keywords: Cable equation; Caputo fractional derivative; Difference scheme; Stability.